Genomic epidemiology and anti-biofilm mechanisms of Lactobacillus in ST11 carbapenem-resistant Klebsiella pneumoniae in China - Shuang Li; Duo Zhang; Duo Zhang; Xindan Zhang; Xindan Zhang; Xiaohan Ma; Xiaohan Ma; Shuai Zheng; Shuai Zheng; Di Zhou; Di Zhou; Qinlong Hou; et al. (Frontiers in Microbiology)
BackgroundThe ST11 clone of carbapenem-resistant Klebsiella pneumoniae (CRKP) has emerged as a major public health threat, driving hospital outbreaks across China and contributing to chronic infections through robust biofilm formation. The scarcity of effective treatment options poses a critical challenge to clinical management.MethodsTo address this issue, we conducted an integrated genomic epidemiological and metabolomic study of ST11 CRKP isolates collected from 13 hospitals in eastern and central China between 2014 and 2020. A total of 2,805 clinical isolates were screened, and 334 ST11 strains were identified using MALDI-TOF mass spectrometry and whole-genome sequencing. Biofilm formation was assessed through microtiter plate assays, while co-culture experiments with Lactobacillus fermentum and Lactobacillus gasseri were performed to evaluate anti-biofilm activity. Scanning electron microscopy (SEM) and non-targeted metabolomics were used to explore structural and metabolic changes.ResultsGenomic analysis revealed alarming resistance rates exceeding 90% to β-lactams, fluoroquinolones, and aminoglycosides among ST11 isolates. Distinct regional distributions of capsular types were observed, with K64 predominant in the east and K47 more common in central China. Biofilm assays showed that 97.6% (326/334) of isolates were biofilm producers. Co-culture with L. fermentum and L. gasseri significantly reduced biofilm biomass by 41.3–58.7% (p < 0.001), and SEM confirmed biofilm structural disruption. Metabolomic analysis revealed that L. fermentum disrupted purine biosynthesis and aminoacyl-tRNA metabolism, while L. gasseri inhibited folic acid synthesis (FDR = 0.017) and the phosphotransferase system.ConclusionThis study reveals critical insights into the clonal spread and biofilm-associated metabolic vulnerabilities of ST11 CRKP. The findings highlight the therapeutic potential of Lactobacillus-based interventions and pave the way for novel probiotic-assisted and plasmid-targeted strategies against antimicrobial-resistant bacteria.